Rankine-Hugoniot relations in turbulent shocks - Gedalin, Michael (Frontiers in Physics, 2023)
A collisionless shock is often regarded as a discontinuity with a plasma flow across it. Plasma parameters before the shock (upstream) and behind the shock (downstream) are related by the Rankine-Hugoniot relations (RH) which essentially are the mass, momentum, and energy conservation laws. Standard RH assume the upstream and downstream regions are uniform, that is, the fluctuations of the plasma parameters and magnetic field are negligible. Observations show that there exist shocks in which these fluctuations remain large well behind the shock. The pressure and energy of these fluctuations have to be included in the total pressure and energy.Here we lay down a basis of theory taking into account persisting non-negligible turbulence. The theory is applied to the case where only downstream magnetic turbulence is substantial. It is shown that the density and magnetic field compression ratios may significantly deviate from those predicted by the standard RH. Thus, turbulent effects should be taken into account in observational data analyses.